ANSWER
The correct answer is D.
EXPLANATION
The given equation of the circle is
[tex] {x}^{2} + {y}^{2} - 6x + 4y - 51 = 0[/tex]
We rewrite to obtain,
[tex] {x}^{2} - 6x + {y}^{2} + 4y = 51[/tex]
We complete the the square to get,
[tex] {x}^{2} - 6x + ( - 3)^{2}+ {y}^{2} + 4y + {(2)}^{2} = 51 +( - 3)^{2} + {(2)}^{2}.[/tex]
[tex] (x - 3)^{2} + {(y + 2)}^{2} = 51 +9+ 4[/tex]
[tex] (x - 3)^{2} + {(y + 2)}^{2} =64[/tex]
[tex] (x - 3)^{2} + {(y + 2)}^{2} = {8}^{2} [/tex]
Comparing to the equation of the circle in standard form
[tex] (x - h)^{2} + {(y - k)}^{2} = {r}^{2} [/tex]
The centre of the circle is
[tex](h,k)=(3,-2)[/tex]
and radius
[tex]r = 8[/tex]
The correct answer is D.